Fiscal disparities in Indonesia in the decentralization era: Does general allocation fund equalize fiscal revenues?. Issue 6 (25th August 2020) - Akita, Takahiro; Riadi, Awaludin Aji; Rizal, Ali
Abstract: This study analyses the level and trend of fiscal disparity among Indonesian districts. It also explores the determinants of fiscal disparity using two inequality decomposition methods: decomposition of the Gini coefficient and the coefficient of variation by revenue sources and decomposition of the Theil index by regions. Disparity in shared revenue has been large due to the very uneven spatial distributions of natural resources and tax bases. It is unambiguously an inequality‐increasing fiscal transfer in Indonesia. A general allocation grant has served to equalize fiscal revenue, but overall fiscal disparity is still high. To reduce the disparity, it may be necessary to modify the general allocation formula since it appears to be defective. This study proposes a new allocation formula. Though the reduction in fiscal disparity is not substantial in the short run, the new formula would provide an incentive for resource‐poorer district governments to raise their own source revenue. This could create a virtuous cycle if the additional own source revenue is used for local development, particularly education and infrastructure. Another option to reduce fiscal disparity would be the further expansion of special allocation grant. If the government allocates the special allocation fund effectively across districts in Indonesia, it could make a special allocation grant an inequality‐decreasing fiscal transfer. Abstract : En este estudio se analiza el nivel y las tendencias de la disparidad fiscal entre los distritos indonesios. También se exploran los determinantes de la disparidad fiscal mediante dos métodos de descomposición de la desigualdad, a saber, la descomposición del coeficiente de Gini y el coeficiente de variación por fuentes de ingresos y la descomposición del índice de Theil por regiones. La disparidad de los ingresos compartidos ha sido grande, debido a distribuciones espaciales muy desiguales de los recursos naturales y las tasas de impuestos. Inequívocamente, en Indonesia esto supone una transferencia fiscal que aumenta la desigualdad. Para igualar los ingresos fiscales se ha empleado una subvención de asignación general, pero la disparidad fiscal general sigue siendo alta. Para reducir la disparidad, podría ser necesario modificar la fórmula de asignación general, ya que parece ser defectuosa. Este estudio propone una nueva fórmula de asignación. Aunque la reducción de la disparidad fiscal no es sustancial a corto plazo, la nueva fórmula proporcionaría un incentivo para que los gobiernos de los distritos más pobres recauden de sus propias fuentes de ingresos. Esto podría crear un círculo virtuoso si los ingresos adicionales de fuentes propias se utilizan para el desarrollo local, en particular la educación y la infraestructura. Otra opción para reducir la disparidad fiscal podría ser la ampliación de las subvenciones de asignaciones especiales. Si el gobierno asigna el fondo de asignación especial de manera efectiva en todos los distritos de Indonesia, podría lograr que la subvención de asignaciones especiales sea un tipo de transferencia fiscal que disminuya la desigualdad. Abstract : 本研究では、インドネシアの地方行政区間の財政格差のレベルと傾向を分析する。また、財政格差の決定要因を、ジニ係数と歳入源別変動係数の分解、テイル指数の地域別分解という、不等式を分解する2つの方法を用いて検討する。分配される税収の格差は、天然資源と課税基盤の分布が空間的に非常に不均一であることが大きな原因である。これは明らかにインドネシアにおける不平等を拡大させる財政移転である。普通交付金は財政収入の平準化に役立ったが、全体的な財政格差は依然として大きい。不均衡を減らすためには、通常の割り当て方式に欠陥があると考えられるため、その修正が必要である可能性がある。本研究では、新しい配分式を提案する。縮小される財政格差は短期的にはそれほど大きなものではないが、新方式では資源の乏しい地方政府が自らの財源収入を増やすためのインセンティブが与えられる。これは、追加的な財源収入が地域開発、特に教育とインフラに使われる場合、好循環が得られる可能性がある。財政の不均衡を是正するもう一つの選択肢は、特別配分を拡大することである。政府が特別配分基金をインドネシアの各地区に効果的に配分すれば、特別配分補助金を、不平等を減少させる財政移転とすることができる。